Transcriptomic Analysis of Fusarium oxysporum Stress-Induced Pathosystem and Screening of Fom-2 Interaction Factors in Contrasted Melon Plants - Yang, Tiantian; Liu, Jiajun; Li, Xiaomei; Amanullah, Sikandar; Lu, Xueyan; Zhang, Mingchong; Zhang, Yanhang; Luan, Feishi; Liu, Hongyu; Wang, Xuezheng (Frontiers in Plant Science, 2022)
Fusarium wilt is one of the most destructive and less controllable diseases in melon, which is usually caused by fusarium oxysporum. In this study, transcriptome sequencing and Yeast Two-Hybrid (Y2H) methods were used for quantification of differentially expressed genes (DEGs) involved in fusarium oxysporum (f. sp. melonis race 1) stress-induced mechanisms in contrasted melon varieties (M4-45 “susceptible” and MR-1 “resistant”). The interaction factors of Fom-2 resistance genes were also explored in response to the plant-pathogen infection mechanism. Transcriptomic analysis exhibited total 1,904 new genes; however, candidate DEGs analysis revealed a total of 144 specific genes (50 upregulated and 94 downregulated) for M4-45 variety and 104 specific genes (71 upregulated and 33 downregulated) for MR-1 variety, respectively. The analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway depicted some candidate DEGs, including Phenylalanine metabolism, phenylpropane biosynthesis, plants-pathogen interaction, and signal transduction of plant hormones, which were mainly involved in disease resistance metabolic pathways. The weighted gene co-expression network analysis (WGCNA) analysis revealed a strong correlation module and exhibited the disease resistance-related genes encoding course proteins, transcription factors, protein kinase, benzene propane biosynthesis path, plants-pathogen interaction pathway, and glutathione S-transferase. Meanwhile, the resistance-related specific genes expression was relatively abundant in MR-1 compared to the M4-45, and cell wall-associated receptor kinases (MELO3C008452 and MELO3C008453), heat shock protein (Cucumis_melo_newGene_172), defensin-like protein (Cucumis_melo_newGene_5490), and disease resistance response protein (MELO3C016325), activator response protein (MELO3C021623), leucine-rich repeat receptor protein kinase (MELO3C024412), lactyl glutathione ligase (Cucumis_melo_newGene_36), and unknown protein (MELO3C007588) were persisted by exhibiting the upregulated expressions. At the transcription level, the interaction factors between the candidate genes in response to the fusarium oxysporum induced stress, and Y2H screening signified the main contribution of MYB transcription factors (MELO3C009678 and MELO3C014597), BZIP (MELO3C011839 and MELO3C019349), unknown proteins, and key enzymes in the ubiquitination process (4XM334FK014). The candidate genes were further verified in exogenously treated melon plants with f. oxysporum (Fom-2, Race 1), Abscisic acid (ABA), Methyl Jasmonite (MeJA), and Salicylic acid (SA), using the fluorescence quantitative polymerase chain reaction (qRT-PCR) analysis. The overall expression results indicated that the SA signal pathway is involved in effective regulation of the Fom-2 gene activity.